Implementation of End User Computing Satisfaction of Sayang Bunda Application - Harsono, Harsono; Iswandhari, Hargianti Dini; Rinayati, Rinayati; Sugiharto, Sigit (Politeknik Ganesha Medan, 2022)
Sayang Bunda application is an application developed by the Semarang Health Office with the aim of preventing (reducing) maternal and infant mortality. This application contains several features; there are assistance, consultation, information on the nearest health facility, pregnancy articles, an estimated day of birth calculator so that this application serves the handling of complaints of pregnant women by doctors or health workers in each area of the of Semarang.. To determine the level of user satisfaction of the application, End User Computing Satisfaction method is used as a measuring tool. The research study conducted in this study was a quantitative-qualitative descriptive study using a cross-sectional research design.. The results showed that on average pregnant women stated 6.9% very dissatisfied, 17.7% dissatisfied, 72.3% satisfied and 1.44% very satisfied with the Sayang Bunda Application that are accompanied by several inputs submitted by pregnant women as users of Sayang Bunda application: It is needed to facilitate the provision of modules for the use of Sayang Bunda application to make it easier for users to interact with the application; it is needed to make variations in coloring the Sayang Bunda application which can have implications of the peculiarities and characteristics of the application Sayang Bunda and it can be facilitated by tutorials on installing applications in smartphones